PELATIHAN IBU-IBU DALAM USAHA PENINGKATAN OLAHAN HASIL TAMBAK UDANG DI DESA BARAKKAH KECAMATAN TIWORO SELATAN KABUPATEN MUNA BARAT - Rejeki, Sri; Libriani, Restu; Tamrin, Tamrin; Faradilla, RH. Fitri; Fajriani Suaib, Yermia Nur; L, Mariani. (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
Barakkah Village coastal communities are still lacking of knowledge, skills and innovation in utilizing local potential especially in the marine sector so that what is sold is only fresh. The purpose of this community service program is to provide assistance so as to increase knowledge, skills and innovation for women in coastal areas in the form of knowledge that is easy to understand so that it is expected to improve the family's economy going forward. Based on the dedication made it can be seen that the response and enthusiasm of the trainees to take part in the training activities is very high as indicated by the fulfillment of the specified number of participants, the good response and enthusiasm of the trainees so as to facilitate the implementation of the program, participants can see firsthand the making of meatballs and shrimp broth in accordance with sanitation and hygiene requirements, participants gain knowledge about how to design packaging and make good and correct packaging and know how to administer of the P-IRT certificate if want to develop a business.